O difícil caminho da reforma: A polícia e os limites do processo de reforma pós-redemocratização - De Souza, Luís Antonio Francisco [UNESP]; Battibugli, Thaís (My University, 2014)
A transition of Brazil from a juridico-political system of exception to a democracy was accompanied by several legal and institutional reform processes, aimed at the gradual elimination of so-called authoritarian rubble and the implementation of instruments of the democratic system, based on recognized citizenship and justice. However, to this day the extent and effects of those reforms can be questioned, especially in light of the increased public demand for justice and citizenship. shows that the route to reform, above all in the sphere of police agencies, is a tortuous one, with an extensive agenda of problems and solutions, demanding research on the part of academics in order to form an understanding of the resistance to change and to new paradigms that define the public security agenda.
The difficult path to reform: The police and limits of the post-redemocratization reform process
Keywords: Police reform; Police violence; Public security; Redemocratization; Security policies